Penyuluhan Kesehatan Tentang Pedoman Gizi Seimbang dan Isi Piringku di SD Inpres Tello Baru - Sididi, Mansur; Nurlinda, Andi; Syahrani, Vadiah; Kurnaesih, Een (PT.Mantaya Idea Batara, 2023)
Knowledge of nutrition is one of the indirect causes of malnutrition. Increasing knowledge through nutrition education can prevent malnutrition and improve human behavior in consuming food according to their nutritional needs, including in school-age children. Good knowledge is a factor that influences a person's attitude and behavior. One of the health promotion activities aimed at increasing knowledge to change people's eating behavior is counseling on balanced nutrition. Activities carried out by the lecture method using poster media. Apart from counseling, games filled my plate were also carried out to evaluate the level of students' knowledge. It can be concluded that nutrition education can increase students' nutritional knowledge about balanced nutrition and plate contents. We hope that we will continue to have a balanced diet and eat the right foods in the future.